ANALISIS YURIDIS PENERAPAN SANKSI PIDANA MATI BAGI PELAKU TINDAK PIDANA PELECEHAN SEKSUAL ANAK DIBAWAH UMUR DAN PEMBEBANAN RESTITUSI KEPADA TERDAKWA - Sintong Hamonangan; Radisman Saragih; Adrianus H. Henok (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Sexual Harassment Crime occurs and is experienced by anyone and minors. Sexual harassment is an act that is really not worth doing because it will have very long-term impacts such as trauma that will be brought to death and also harm the victim’s family. Sexual Harassment can be committed by anyone, including Islamic boarding school teachers as stated in Decision No. 86/Pid.sus/2022/PT.Bdg, the research method to be used is based on the author’s analysis in imposing the sentence that should be decided. A pesantren teacher who has sexually abused 13 children under the age of this victim is very cruel and indecent treatment for an educated pesantren teacher, therefore the perpetrator must be held responsible for his actions with appropriate punishment.